Ni hablar, ni pensar, ni soñar. Análisis histórico de su transformación en unidades fraseológicas - Pérez Salazar, Carmela (El Colegio de México, 2009)
This paper deals with the diachronic analysis of three sequence formulas of contemporary Spanish: ni hablar (de eso), ni pensar(lo), ni soñar(lo) [neither speak (about it), think (of it), nor dream (of it)]. These agree in their structure, in the nature of its integrating elements, and in its idiomatic meaning. By revising the historical presence of each of them in our language, I pretend to discover not only the transformation stages they undergo −until they reach their modern condition of phraseological units−, but specially the common motivation that gave origin to their use as such formulas.